2015
DOI: 10.1080/13102818.2015.1056230
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms in periodontitis. Overview

Abstract: Today, it is known that pathogenic bacteria are the key factors for the initiation of periodontal disease, but the host response and the severity of clinical expression are largely determined by genetic susceptibility and environmental factors. There is evidence that the individual response to the environment and variations in the immune response in periodontitis are associated with genetic factors. Of particular interest are the polymorphisms of interleukin-1 beta (IL-1b), interleukin-6 (IL-6) and tumour necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
3
0
1
Order By: Relevance
“…As the primary response to pathogens in our innate immune system is mainly triggered by Toll-like receptors (TLRs), a lot of research has noted that polymorphisms in TLRs genes were associated with PD [22][23][24] (Figure 3). ity [17][18][19]. Defensins are antimicrobial peptides, crucial components of innate immunity, and extensively present in our oral environment.…”
Section: Evidence Of Epigenetic Modifications (Polymorphism Gene Expr...mentioning
confidence: 99%
See 1 more Smart Citation
“…As the primary response to pathogens in our innate immune system is mainly triggered by Toll-like receptors (TLRs), a lot of research has noted that polymorphisms in TLRs genes were associated with PD [22][23][24] (Figure 3). ity [17][18][19]. Defensins are antimicrobial peptides, crucial components of innate immunity, and extensively present in our oral environment.…”
Section: Evidence Of Epigenetic Modifications (Polymorphism Gene Expr...mentioning
confidence: 99%
“…It was observed that allelic variants at multiple genetic loci probably influence its susceptibility [ 16 ]. Many reports have demonstrated that pro-inflammatory cytokines play a significant role in the pathogenesis of PD and single-nucleotide polymorphisms (SNPs) in their genes were strongly linked to the risk for the disease and its severity [ 17 , 18 , 19 ]. Defensins are antimicrobial peptides, crucial components of innate immunity, and extensively present in our oral environment.…”
Section: Historical Evidence In the Association Between Genetics And ...mentioning
confidence: 99%
“…In particular, genes encoding for mediators involved in host immunity and metabolism such as cytokines and cell-surface receptors ( 72 ). Any dysregulation in genetic expression of these mediators might result in persistent destructive inflammation of the periodontium and the development of periodontitis ( 73 ). Accordingly, the association of particular SNPs with periodontitis differs among various populations and ethnic groups ( 67 ).…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Aunque, comercialmente, existen pruebas que determinan la susceptibilidad de los pacientes a desarrollar periodontitis basados en polimorfismos de la IL-1B; la especificidad de los marcadores genéticos asociados con el incremento de la producción de la IL-1β sigue siendo de interés para la comunidad científica, debido a su correlación con la gravedad de la periodontitis; y a que aún no es claro el mecanismo y la influencia de factores tales como la etnicidad sobre la especificidad y sensibilidad de estas pruebas (8) ; dado que estas han sido evaluados sólo en ciertos grupos poblacionales (9) .…”
Section: Mensajes Clave Introducciónunclassified